Interpreting the athlete`s ECG: Current state and future perspectives - Basu, J.; Malhotra, A. (Current Treatment Options in Cardiovascular Medicine, 2018)
Sudden cardiac death (SCD) is the leading cause of death in athletes. A large proportion of these deaths are associated with undiagnosed cardiovascular disease. Screening for high-risk individuals enables early detection of pathology, as well as permitting lifestyle modification or therapeutic intervention. ECG changes in athletes occur as a result of electrical and structural adaptations secondary to repeated bouts of exercise. Such changes are common and may overlap with patterns suggestive of underlying cardiovascular disease. Correct interpretation is therefore essential, in order to differentiate physiology from pathology. Erroneous interpretation may result in false reassurance or expensive investigations for further evaluation and unnecessary disqualification from competitive sports. Interpretation of the athlete`s ECG has evolved over the past 12 years, beginning with the 2005 European Society of Cardiology (ESC) consensus, progressing to the ESC recommendations (2010), Seattle Criteria (2013) and the `refined` criteria (2014). This evolution culminated in the recently published international recommendations for ECG interpretation in athletes (2017), which has led to a significant reduction in false positives and screening-associated costs. This review aims to describe the evolution of the current knowledge on ECG interpretation as well as future directions.